Virtual museums: concept and settings (Cadernos de Sociomuseologia, 2018)
Museums also seek to bring to the public information about the content of their collection and the cultural activities developed in their space. The use of the Internet as a means of communication made it possible for museums to interact more closely with the public - whether or not they were in museums. But what are virtual museums? What sets them apart from museum sites? This article focuses on the configuration of virtual museums, discussing their concept based on authors who worked on the theme. In addition, it presents two examples of virtual museums: the Portinari Project and the MUVA.Key-words: virtual museum; museum; internet; cibermuseum; virtual